2021
DOI: 10.1089/ast.2020.2252
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Calcium Perchlorate on the Search for Organics on Mars with Tetramethylammonium Hydroxide Thermochemolysis

Abstract: The Mars Organic Molecule Analyzer (MOMA) and Sample Analysis at Mars (SAM) instruments onboard the Exomars 2022 and Mars Science Laboratory rovers, respectively, are capable of organic matter detection and differentiating potentially biogenic from abiotic organics in martian samples. To identify organics, both these instruments utilize pyrolysis-gas chromatography coupled to mass spectrometry, and the thermochemolysis agent tetramethylammonium hydroxide (TMAH) is also used to increase organic volatility. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Perhaps most importantly, TMAH appears to be better suited for samples containing perchlorates. He et al (2021b) demonstrated that up to 5 wt% of calcium perchlorate did not significantly impact the recovery of free fatty acids at a concentration of 300 ppb. In situ analysis with TMAH at Mars has been performed; however, data analysis is, at this moment, ongoing (Roach et al, 2021).…”
Section: Gas Chromatographymentioning
confidence: 95%
See 1 more Smart Citation
“…Perhaps most importantly, TMAH appears to be better suited for samples containing perchlorates. He et al (2021b) demonstrated that up to 5 wt% of calcium perchlorate did not significantly impact the recovery of free fatty acids at a concentration of 300 ppb. In situ analysis with TMAH at Mars has been performed; however, data analysis is, at this moment, ongoing (Roach et al, 2021).…”
Section: Gas Chromatographymentioning
confidence: 95%
“…Limited validation of the one-pot methodologies for COSAC, SAM, or MOMA has been published. Nonetheless, a multitude of demonstration and qualitative studies have been performed with flight-like sample chambers coupled to commercial GC-MS systems where pyrolysis, derivatization, or thermochemolysis were applied (e.g., Lewis et al, 2018;Reinhardt et al, 2020;He et al, 2021b). Whereas the one-pot derivatization methodology is versatile, it also adds risk.…”
Section: Gas Chromatographymentioning
confidence: 99%
“…The SAM-like ramp pyrolysis is the same as in previous work [32,33]. In this process, a cup containing the sample was heated using heart-cut EGA temperature zones from 50 °C to reach the final temperature (850 °C held for 1 min) at the SAM heating rate of 35 °C min -1 .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Both of these approaches are currently being employed by SAM onboard the Curiosity rover as part of the MSL mission (Mahaffy et al, 2012;Williams et al, 2019;Millan et al, 2021, accepted) and by the MOMA instrument (Goesmann et al, 2017;Mißbach et al, 2019;Reinhardt et al, 2020). Some methods (e.g., derivatization approaches) may be sensitive to some salts and water (Freissinet et al, 2015;Mißbach et al, 2019) while others (e.g., TMAH thermochemolysis) are more tolerable of both (Mißbach et al, 2019;He et al, 2021). Thus, sample matrix composition for Martian and other astrobiology targets, particularly the briny, ice-covered oceans harbored by moons of the outer planets, may require instruments to adapt new hardware, methods, and operations for salt-laden samples (e.g., addition of desalting or dilution steps).…”
Section: Ionization Sources and Molecular Separation Techniquesmentioning
confidence: 99%